An Analysis of the Major Themes in Khaled Hosseini’s Novel “The Kite Runner” (Research, Society and Development, 2020)
This study aims to analyze the major theme in The Kite Runner novel, by Khaled Hosseini. In line with the previous research problem, the objective is to find out and describe the process of major themes analysis in the novel. This research was conducted based on developmental research.  This research is qualitative research which employed documentation as the data collection. In this analysis the writer found several major themes, namely, friendship (fathers and sons); betrayal and guilt; redemption and friendship. In every conflict there’s an easy choice, and then there’s the right choice. This is a story of redemption where a boy takes the easy path, and pays for it, until he can finally become a man and right what he has wronged.